Institutional investors, climate policy risk, and directed innovation - Marie-Theres von Schickfus (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
The tightening of climate policies may cause technologies based on fossil fuels to lose value compared to "green" technologies. For firms with significant fossil-based knowledge, this implies that their firm (market) value is at risk. This technological risk is also relevant for financial market actors, in particular institutional investors following long-term investment strategies. Measuring technological knowledge using patent data at the firm level, this paper uses a dynamic patent count data model and explores whether institutional investors address technological transition risk via engagement activities. Despite robust evidence for a positive influence of institutional investors on overall innovation, no evidence can be found that institutional ownership is associated with a change in the direction of innovation.
Keywords: Q55; G23; O34; 330; Green innovation; green finance; climate policy; climate risk; institutional investors